Association of self-care status with some relevant factors in middle-aged women in their early menopausal stage - Mahboobeh Kafaei Atrian; Mahnaz Solhi; Farbod Ebadi Fard Azar; Fatemeh Atoof (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Through self-care, people can solve their health-related problems through increasing their awareness and correcting their lifestyles. OBJECTIVES: To determine the association of self-care status with some relevant factors in Kashanian middle-aged women in their early menopausal stage. METHODS: This is a cross-sectional study on 351 women in the age range of 45-60 years. Women were selected based on cluster sampling method from the individuals at health-care centers in Kashan, Iran. Researcher-constructed questionnaire on self-care was used. The validity and the reliability of the questionnaire were calculated. The information gathering method was questionnaire completion by the study participants or interview with them. Collected data were analyzed with SPSS 16 software. T-test, ANOVA, Spearman correlation, and linear regression analysis were applied. RESULTS: The mean (±standard deviation) of the self-care score was 108.14 ± 20.43. Self-care scores were weak in 13.92%, intermediate in 71.02%, and good in 15.06%. Regression analysis showed that the mean of self-care was significantly higher in those with higher educational level of women's (P = 0.045) and their spouses (P = 0.001). Women who were covered by insurance also showed higher self-care; in addition, there was no significant relationship between self-care and participants' job, spouses' jobs, marital status, marital satisfaction, economic satisfaction, number of children, number of households, and type of accommodation (P > 0.05). CONCLUSION: The results indicate that self-care is inadequate and that the level of education of couples and insurance coverage has a positive effect on the level of self-care in postmenopausal women. To promote self-care in old age, education and empowerment can be considered.